FAMILY CENTERED MATERNITY CARE (FCMC) SEBAGAI UPAYA SKRINING/DETEKSI DINI KEHAMILAN RISIKO TINGGI BERBASIS KELUARGA DI PUSKESMAS ABELI - Hasniah Dina; Ari Nofitasari; Dewi Sari Pratiwi; Apriyanti Apriyanti; Nazaruddin Nazaruddin (Universitas Mataram, 2026)
The maternal mortality rate (MMR) remains an important health indicator that requires serious attention, particularly at the primary healthcare level. One of the contributing factors to the high MMR is the delay in recognizing danger signs and high-risk conditions during pregnancy. The Family Centered Maternity Care (FCMC) approach is a healthcare strategy that emphasizes the active involvement of families in the early detection of pregnancy risks, maternal care, and decision-making related to maternal health. This community service activity aimed to improve the knowledge and skills of families in conducting high-risk pregnancy screening through the FCMC approach in the working area of Abeli Primary Health Center. The activity was conducted through a one-day education and training program involving families of pregnant women in the Abeli Primary Health Center area. The methods included health education sessions, group discussions, simulations on identifying pregnancy danger signs, and the distribution of educational media, followed by pre- and post-intervention knowledge evaluations. The results showed that among 21 participants, before the health education was provided, 7 participants (33.33%) had good knowledge and 14 participants (66.67%) had poor knowledge. After the educational intervention, 16 participants (76.19%) had good knowledge and 5 participants (23.81%) had poor knowledge. These findings indicate an improvement in family knowledge regarding pregnancy danger signs and high-risk factors after receiving education and training. In addition, there was increased understanding of the family’s role in supporting early detection and maternal health decision-making. A WhatsApp group was also established to facilitate communication and coordination with healthcare workers. The FCMC approach improves family knowledge and involvement in screening for high-risk pregnancies and helps prevent complications as part of a promotive and preventive strategy in primary healthcare services.